Common Threads : Steelcase and ARZU's Market-Led Approach to Create Employment Opportunities for Women Weavers in Afghanistan - World Bank (Washington, DC, 2017)
ARZU, a Chicago-based Non-governmental Organization (NGO), was founded on the goal to apply a market-led approach for sustainable poverty alleviation achieved through artisan-based employment that empowers women. Focusing on Afghan women, the organization identified rug weaving as an employment opportunity that fit within the cultural framework and limitations for women that exist in the country. To begin the initiative in 2004, ARZU hired local staff based in Kabul, and they began to meet with village elders and explain what they wanted to do and ask for permission, taking into account the cultural norms of Afghan society. ARZU uses a combination of donations and the proceeds from sales to fund its social programs and pay the weavers fair market wages. It also covers the cost of local staff to ensure quality control, train weavers to improve techniques, and manage the distribution channels. Currently, ARZU's sales fund 50 percent of its social programs, and the organization hopes to be fully financially sustainable in the next several years. Steelcase and ARZU's partnership illustrates the realized potential of what can happen when an NGO and a corporation overlap in their strategic vision and goals and work together to create job opportunities for the poor. In this partnership, Steelcase accepted a product development cycle that was nearly six months longer to support employment in Afghanistan. As ARZU continues to forge new corporate clients and steelcase continues to seek new partnerships that employ workers in developing countries, a key lesson learned from this private sector-NGO partnership is that it is feasible for a corporation to contract out to social enterprises without lowering quality standard or significantly affecting profitability.